The writings of Bobby Sands : a collection of prison writings by H-Block hunger-striker Bobby Sands - Sands, Bobby; Adams, Gerry (Dublin : Sinn Féin Informations Office, 1981)
Bibliotheek François Vercammen
Engels
Brochure